2008
DOI: 10.1080/03008200802143166
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Reactive Oxygen Species in Integrin and Matrix Metalloproteinase Expression and Function

Abstract: Cell adhesion and migration is largely dependent on integrin binding to extracellular matrix, and several signalling pathways involved in these processes have been shown to be modified by reactive oxygen species (ROS). In fact, integrin activation is linked to increased ROS production by NADPH-oxidases, 5-lipoxygenase, and release from mitochondria. Cell migration is intimately linked to degradation of the extracellular matrix, and activated matrix metalloproteinases (MMPs) are a prerequisite for cancer cell i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 64 publications
2
65
0
3
Order By: Relevance
“…This mechanism also requires the activity of irg1-like, a second zebrafish homologue of the mammalian Irg1 (36). ROS species can function as signaling molecules to regulate the transcription and activity of various inflammatory mediators, including matrix metalloproteinases (70,92), which contribute to macrophage recruitment during inflammatory processes of the skin (36). However, the mechanisms discovered in these studies have not yet been confirmed in mammalian cells.…”
Section: Subcellular Localization Of Mammalian Cad/irg1mentioning
confidence: 90%
“…This mechanism also requires the activity of irg1-like, a second zebrafish homologue of the mammalian Irg1 (36). ROS species can function as signaling molecules to regulate the transcription and activity of various inflammatory mediators, including matrix metalloproteinases (70,92), which contribute to macrophage recruitment during inflammatory processes of the skin (36). However, the mechanisms discovered in these studies have not yet been confirmed in mammalian cells.…”
Section: Subcellular Localization Of Mammalian Cad/irg1mentioning
confidence: 90%
“…Integrin signaling also facilitates cell proliferation and migration, which is intimately linked to the degradation of the extracellular matrix, and activated MMPs are a prerequisite for cancer cell invasion (46). We established that the plasma level of MMP9 increases approximately 2 times even in the early stage of cancer development and approximately 3.5 times in the terminal stage (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…The oncogenic miRNAs, secreted by cancer cells into the environment, are considered a primary mediator of this process (44,45). The activation of integrins is linked to additional ROS/RNS production by NADPH oxidases, lipoxygenases, mitochondria, etc., leading to a vicious cycle (46). As a result, the antioxidant defense system crashes with the progression of cancer and tissue redox balance shifts toward oxidation in the intermediate/terminal stage (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Likely, when H2O2 is produced at high concentrations in MDA-MB 231 cells, it may be capable to affect enzymatic activities by altering signaling pathways and even cause cellular damage. Many elements in the process leading to cell migration are considered to be redox-sensitive (Pani et al, 2009;Svineng et al, 2008). ROS modify the activity of several key enzymes, resulting in the reorganization of actin cytoskeleton, adhesion and stimulation of migration.…”
Section: Cell Migration Is Influenced By H2o2 Levelsmentioning
confidence: 99%